Functionalization of graphene by a TPE-containing polymer using nitrogen-based nucleophiles. Issue 24 (24th May 2016) - Tu, Jin; Zhao, Min; Zhan, Xuejun; Ruan, Zhijun; Zhang, Hao-Li; Li, Qianqian; Li, Zhen
Abstract : Through the nitrogen-centered anion reaction of PCT and GO, two new hybrids, RGO-PCT-i and RGO-PCT-s, were successfully prepared and applied as potential optical limiting materials. Abstract : On the basis of the nitrogen-centered nucleophilic reaction of GO and the carbazole derivative in a TPE-containing conjugated polymer of PCT, new RGO-based hybrids have been prepared, separated by centrifugation, and characterized by IR, TEM, SEM, UV-Vis absorption spectra, XRD, Raman and TGA. Thanks to the twist structure of the TPE in PCT, RGO-PCT-s, the soluble RGO hybrid with small sheets of a size of about 500 nm, showed good dispersibility and dispersion stability in aqueous solution. RGO-PCT-i, the insoluble RGO hybrid with a larger size, demonstrated a better optical limiting (OL) response than its individual counterparts. In comparison with individual GO and PCT, efficient photo-induced electron transfer (PET) and energy transfer (ET) processes between the PCT and RGO moieties and reduction of GO offered RGO-PCT-i a much larger optical limiting performance, as low as 18.8%, at the same mass concentration with the open-aperture Z -scan at 532 nm with 8 ns laser pulses.